Contrastive Analysis of Kala/Time Adverbs in Indonesian and Zharaf Zaman in Arabic - Imaduddin*, M.; Zihadi, Lalu M. Shulhan (Riwayat: Educational Journal of History and Humanities, 2023)
The following article examines the contrastive analysis of tenses/time adverbs in Indonesian and zharaf era in Arabic. The aim of this research is to analyze the comparison of Zharaf Zaman in Arabic with time information in Indonesian in terms of form and use in sentences in each language. The following research is included in the library study group, the method used is the comparative method which is one of the linguistic sciences which discusses the comparison of two or more languages or sub-systems of a number of languages, which aims to find differences and similarities between the two languages. Then the analysis used in the following research is the descriptive analysis method. The results of the following study are that in terms of form, there are similarities between the zharaf of the era and the description of time, namely in the form of single words, idhafah and jar letters. And the difference between the two is in terms of jamid and musytaq. The forms jamid and musytaq are only found in Arabic. In terms of its use in sentences, both zharaf era and time information have similarities and differences in terms of location, nashab, use in interrogative sentences and so on.